The forwarder planning problem in a two‐echelon network. Issue 4 (29th September 2019) - Di Francesco, Massimo; Gaudioso, Manlio; Gorgone, Enrico; Zuddas, Paola
Abstract: This paper is motivated by the case of a forwarder dealing with inland transportation planning, from a seaport, of inbound containers filled with pallets having different destinations in the land‐side. Although the forwarder is not the owner nor controls any vehicle, he is required to plan both the assignment of containers to intermediate depots, where the pallets are unpacked, and the assignment of pallets to the vehicles used for the distribution from depots to consignees. We present a mathematical model supporting the forwarder in this two‐echelon network to minimize assignment costs, while accounting for a balanced workload among all carriers involved in this distribution scheme. We discuss a tailor‐made implementation of the model in a realistic context and present a heuristic method to solve realistic‐sized instances. Our computational experiments confirm the viability of this method.